Analysis of the production processes of the Pamplona confectionery sector as a platform for industrial and business development - Jaimes Villamizar, Vianeth Socorro; Peñaranda Ayala, Zoraima Victalia; Castro Escobar, Sandra Milena (Ingeniería Solidaria, 2025)
The article is derived from the research titled “Analysis of the Production Processes of the Pamplona Candy Market as a Platform for Industrial and Business Development,” conducted at the University of Pamplona in 2004. Introduction: The creation of a strategic plan was essential for fostering business development in the competitive Pamplona candy market. This process involved a thorough analysis of the market, competition, and consumer trends. The goal was to evaluate the production processes within the Pamplona candy market to identify areas for improvement and propose strategies that would optimize efficiency, promote business growth, and enhance competitiveness. Problem: The candy market is a crucial economic activity in Pamplona, contributing significantly to the local economy and providing employment. However, it faces challenges related to modernization, competitiveness, and long-term sustainability. Methodology: The research employed a mixed-methods approach, combining both qualitative and quantitative methods. This approach was vital for designing a comprehensive strategic plan. The qualitative analysis provided insights into the dynamics of the sector, while Porter’s Five Forces analysis helped assess the competitive landscape. By integrating both methods, we were able to formulate strategies to enhance the sector’s competitiveness. Results: The survey revealed that the sector is primarily dominated by micro-businesses, emphasizing their critical role in the local economy. The findings allowed us to design a strategic plan aimed at strengthening their competitive growth and establishing the candy market as a platform for sustainable business development in Pamplona. Conclusion: Companies in the candy sector must focus on innovation by creating healthier products, improving digital marketing strategies, and leveraging e-commerce to adapt to market trends. This will enable them to expand into new markets and channels, enhancing their competitiveness in the evolving business landscape.